Bone Metastasis in Primary Endometrial Carcinoma: Features, Outcomes, and Predictors. Issue 1 (1st January 2014) - Yoon, Aera; Choi, Chel Hun; Kim, Tae-Hyun; Choi, June-Kuk; Park, Jin-Young; Lee, Yoo-Young; Kim, Tae-Joong; Lee, Jeong-Won; Bae, Duk-Soo; Kim, Byoung-Gie
Abstract : Objectives: This study aimed to describe the clinicopathologic characteristics and outcomes and to assess the predictors associated with prognosis in endometrial carcinoma that developed bone metastasis. Methods: A retrospective review of medical records was performed to identify the patients with endometrial carcinoma who developed bone metastasis between October 1994 and May 2012. Results: Of the 1185 patients with endometrial carcinoma, 22 (1.8%) were identified with bone metastasis, and 21 patients were analyzed in the study. Seventeen (80.9%) patients had advanced-stage disease (2009 International Federation of Gynecologists and Obstetricians stages III-IV). Four (19.0%) patients had a bone lesion at the diagnosis of endometrial cancer. The median time of recurrence to the bone in 17 patients was 9 months (range, 2–43 months). The median overall survival (OS) and survival after bone metastasis of the entire cohort were 33 months (range, 9–57 months) and 15 months (range, 12–17 months), respectively. The patients with bone metastasis at recurrence had significantly longer OS than those patients with bone metastasis at diagnosis of endometrial cancer (36 vs 13 months; P = 0.042). Metastasis to extrapelvic bone was significantly associated with longer OS (46 vs 19 months; P = 0.001) and longer survival after bone metastasis (25 vs 12 months; P = 0.002). Isolated bone recurrence without extraosseous metastases and extrapelvic bone metastasis revealed independent predictors for survival after bone metastasis (hazard ratio, 0.09; 95% confidence interval, 0.01–0.67; P = 0.019 and hazard ratio, 0.07; 95% confidence interval, 0.01–0.53; P = 0.01). Conclusions: In endometrial carcinoma that develops bone metastasis, isolated bone recurrence and extrapelvic bone metastasis are significant predictors of prolonged survival after the diagnosis of bone metastasis. Further researches on the optimal treatment modality and factors that have the clinical implications are warranted.